Immunogenicity Assessment of Pegfilgrastim in Patients with Breast Cancer - Yu. V. Medvedev; M. A. Kolganova; O. A. Sas; T. N. Komarov; E. N. Fisher; I. E. Shohin; Yu. I. Ammour (Разработка и регистрация лекарственных средств)
Introduction. Neutropenia, which is an abnormally low concentration of neutrophils in the blood, is one of the common side effects in patients receiving radio- or chemotherapy. Neutropenia usually leads to higher risks of severe bacterial and fungal infections. Such medicines as colonystimulating factor filgrastim (and its conjugates) are used to prevent and treat neutropenia in oncology patients. Immunogenicity is a potential concern for any biological product, thus, its assessment is one of the most critical necessities during the development and registration of such products.Aim. The main aim of this study was to validate the ELISA method for anti-pegfilgrastim antibodies detection in human serum samples and to apply the validated method to pegfilgrastim drugs immunogenicity assessment.Materials and methods. To assess pegfilgrastim immunogenicity, the commercial ELISA kit «PEGylated Filgrastim (Neulasta®) ADA ELISA» was used for screening, confirmatory and titer assay. Moreover, to confirm the chosen commercial kit suits the study aims it was revalidated. The absorbance values were obtained using plate immunoassay analyzer Stat Fax 3200, plate washing was performed using an automatic twochannel plate washer.Results and discussion. The ELISA method for anti-pegfilgrastim antibodies determination in human serum samples was validated and applied to the analytical part of the comparative, multicenter, blind, randomized study of pegfilgrastim efficacy and safety in patients with breast cancer, receiving myelosuppressive chemotherapy. Human serum samples were first screened for anti-drug antibodies, then «screening positive» samples were analyzed in confirmatory assay with % inhibition calculation for each sample. The «confirmed positive» samples were further characterized in titer assay.Conclusions. The ELISA method for anti-pegfilgrastim antibodies determination in human serum samples was successfully validated and applied for pegfilgrastim drugs immunogenicity assessment.